The fever code - Dashner, James, 1972- (Dashner, James, 1972- Maze runner series., 2016)
After the forests burned, after the lakes and rivers dried up, and the plagued killed entire families, the Wicked searched for an answer to the dying the world. Then they found a boy named Thomas who would build a maze that would become the link between life and death; a maze only he could tear down. This is the story of how he created that maze, and the lies and secrets it birthed.